2020
DOI: 10.1155/2020/8822859
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in Nonalcoholic Fatty Liver Disease: Potential Diagnosis and Prognosis Biomarkers

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common chronic liver disease worldwide in part due to the concomitant obesity pandemic and insulin resistance (IR). It is increasingly becoming evident that NAFLD is a disease affecting numerous extrahepatic vital organs and regulatory pathways. The molecular mechanisms underlying the nonalcoholic steatosis formation are poorly understood, and little information is available on the pathways that are responsible for the progressive hepatocellular da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 134 publications
(158 reference statements)
1
49
0
2
Order By: Relevance
“…In our hands too, the HepG2 cells express GLP-1R (data not shown). Although LncRNAs usually do not translate into proteins, they regulate protein-coding genes and related signaling pathways involved in multiple diseases [ 34 ], including NAFLD [ 3 ]. Our data shows that there were differences in LncRNA expression profiles between untreated and steatotic HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our hands too, the HepG2 cells express GLP-1R (data not shown). Although LncRNAs usually do not translate into proteins, they regulate protein-coding genes and related signaling pathways involved in multiple diseases [ 34 ], including NAFLD [ 3 ]. Our data shows that there were differences in LncRNA expression profiles between untreated and steatotic HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found 56 and 123 LncRNAs that were respectively upregulated and downregulated in Ex-4-treated steatotic cells relative to steatotic cells. The function of several of the differentially expressed LncRNAs in our study is unknown, while many others are known to be associated with different diseases such as cancer [ 35 ], and a set of them was previously associated with NAFLD [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-chromosome inactivation (XCI), which refers to the random selection and transcriptional silence of one of two X-chromosomes in females at the early stages of embryonic development, is a unique dosage compensation mechanism in mammals (Waldron, 2016;Bar et al, 2019;Strehle and Guttman, 2020;Yu B. et al, 2020). In most placental mammals, there are two waves of XCI: the imprinted XCI exists in the fertilized embryo and extraembryonic tissues, and the random XCI persists in the inner cell mass (after implantation around embryonic day 5.5), yet humans lack the imprinted XCI and instead have X chromosome dampening (XCD) (Ropers et al, 1978;Harper et al, 1982;Kung et al, 2013;Lee et al, 2013; van Bemmel et al, 2016;Finestra and Gribnau, 2017;Sahakyan et al, 2018).…”
Section: The Role Of Lncrna Xist In X Chromosome Dosage Compensationmentioning
confidence: 99%
“…Noncoding RNAs are a group of RNA molecules without protein-coding capacity, involved in chromatin remodeling and in transcriptional and post-transcriptional gene regulation [ 23 ]. Among noncoding RNAs, especially the microRNAs (miRNA) are deregulated in NAFLD, and several studies have shown the association of miRNAs with liver steatosis [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%